Initiation-Response-Feedback Pattern Used by Lecturer-Students in EFL Classroom Interaction - Kartini Kartini; Sitti Syakira; Sitti Aisyah (TLEMC (Teaching and Learning English in Multicultural Contexts), 2022)
Applying a descriptive qualitative method with case study design, this research aimed at finding and describing how initiation-response-feedback take place in classroom interaction. The data collection was done through observation conducted in two classes of the third-year students of English Education Department in one of the state universities in Makassar. The observation was conducted three times in each class. Analyzed using discourse analysis, the results show that in term of initiation, four subclasses were used by the lecturer namely requestives,descriptives, elicitation, and informatives. In term of students’ responding act, students used three subclasses features namely positive responding act, negative responding act, and temporization. As for follow-up, the lecturer used three subclasses features namely endorsement, concession, and acknowledgment. This research also found that acknowledgment was used to repair and accept with repair student’s response. Classroom interaction took place by using subclasses of head act. The lecturer uttered initiation based on the function of each subclasses. That was similar to how students’ responding act took place which was based on lecturer initiation. Furthermore, the lecturer responded students’ in many ways based on the responding act. Hence, it should be pointed out that a turn can be made up not only of a single move, but also of two moves: it can be either a combination of a responding and an initiating move, or a follow-up and an initiating move. However, initiation moves, response moves and follow-up moves cannot be separated each other since it was three-part exchange in classroom interaction. Keywords: Initiation-Response-Feedback, Lecturer’s Initiation and Feedback, Students’ Response, EFL Classroom Interaction